Poor Community with Long Life Expectancy - Surjono, Gunanto (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Living on a remote island usually associated in general with poverty, far from food adequacy, limited health service, low life resources diverification, and poor mobile facility to go out of their island. But people form Giliyang Island, Sumenep Regency, Madura, East Java Province, show themselves different form general association. They, who have been living through generations and relatively poor, have high life expectancy, far longer from national life expectancy level. Through interview with several public and non-formal figures, field observation, and documentary analysis, found that elderly people looked more dominant in number than other age groups, yet they lived in fresh and healthy condition. More insight on the island and its people revealed that oxygen deposit and its explosion on the island were very high (highest in the world), bringing the air clean and fresh, inhaled everyday and for a long time by the locals inhabiting the island, made the people avoid from disease caused be polluted air, looking fresh, healthy, and long life.